Biharmonic Constant ?1-Slope Curves according to Type-2 Bishop Frame in Heisenberg Group Heis3 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2014)
In this paper, we introduce constant Pi(1)-slope curves according to type-2 Bishop frame in the Heisenberg group Heis(3). We characterize the biharmonic constant Pi(1)-slope curves in terms of their Bishop curvatures. Finally, we find out their explicit parametric equations in the Heisenberg group Heis(3). Additionally, we illustrate our main theorem.
Keywords: Biharmonic curve; type-2 Bishop frame; Heisenberg group